Secondary Education English Final Exam, Teaching and TestingControversies: Third year Students, Bechar (Numerus academy review, 2026)
This work is an attempt to analyse the final secondary exam (BAC) in terms of itsresponse and compliance with the educational, pedagogical and didactical requirementsof the method being applied in the Algerian school. Competency-Based Approach (CBA)has been carefully selected and applied to meet the policy maker’s ends. Questionnairesare the main tool for data collection, in addition to the comparative analysis used to critically compare two exam samples belonging to different Algerian educational periodsin order to find out the differences and similarities that might be between them. The research shows that teachers of English find the exam incomplete since it does not consider testing oral competency. Moreover, there is a very slight difference foundbetween the two exam samples although they had been designed on the grounds of twodifferent methods to EFL teaching. An overlap is apparently characterising the learningoutcomes of CBA with the final official exam (BAC) objectives in Algeria.